2016
DOI: 10.5020/18061230.2016.p51
|View full text |Cite
|
Sign up to set email alerts
|

Conceitos, causas e repercussões da violência sexual contra a mulher na ótica de profissionais de saúde

Abstract: Concepts, causes and repercussions of sexual violence against women from the perspective of healthcare professionals Conceptos, causas y repercusiones de la violencia sexual contra la mujer a partir de la opinión de profesionales sanitarios RESUMO Objetivo: Analisar os sentidos atribuídos por profissionais de saúde aos conceitos, causas e repercussões da violência sexual contra a mulher. Método: Estudo qualitativo realizado com 68 profissionais de saúde de nível superior integrantes de equipe multiprofissional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
3
0
7
Order By: Relevance
“…There are cultural resistances in approaching the issue with patients, prevailing the biological model, to the detriment of the precepts of integrality, often attributing the recognition of SA to physical and superficial injury. 25,[29][30][31] Given this premise, the need for qualification of vocational training focusing on the social and health interests of the population is considered. For this, it is important to ensure the insertion of the topic gender violence, and its different expressions, in the minimum curriculum, based on the need of the community, recognizing that the HEIs have an important role to broaden the discussion in academic spaces and enable the understanding of unequal construction between genders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are cultural resistances in approaching the issue with patients, prevailing the biological model, to the detriment of the precepts of integrality, often attributing the recognition of SA to physical and superficial injury. 25,[29][30][31] Given this premise, the need for qualification of vocational training focusing on the social and health interests of the population is considered. For this, it is important to ensure the insertion of the topic gender violence, and its different expressions, in the minimum curriculum, based on the need of the community, recognizing that the HEIs have an important role to broaden the discussion in academic spaces and enable the understanding of unequal construction between genders.…”
Section: Discussionmentioning
confidence: 99%
“…For this, it is important to ensure the insertion of the topic gender violence, and its different expressions, in the minimum curriculum, based on the need of the community, recognizing that the HEIs have an important role to broaden the discussion in academic spaces and enable the understanding of unequal construction between genders. 30,31 There is a certain lack about the inclusion of content that discuss the SA identified from the students' experiences during disciplinary practices. However, HEI managers considered the multidisciplinarity that surrounds the topic and revealed that the content approach is transversal in the undergraduate course, besides being also contemplated in some research and extension strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ver if ica-se, ainda, que a f ragilidade da qualif icação prof issional 15,19,22,23 para esse t ipo de atuação é intensif icada pel a f alta de treinamento no contex to dos ser v iços 15,16,20,21 , contr ibuindo para uma ...refletir estratégias destinadas a envolver diversos segmentos para a resolução do problema...…”
Section: Resultsunclassified
“…Ao considerar a impotênc ia perante os casos de v iolênc ia se compreende a necessidade dos prof issionais em termos de capac itação sobre gênero 16,21 , para proporc ionar autonomia e atuação efet iva diante de tais situações, não se restr ingindo ao encaminhamento, diante da ausênc ia de agravos f ísicos 16,22 e/ou atendimento esporádico 25,26 . Essas condutas são heranças de uma formação prof issional incipiente diante de questões de cunho social e psicológico...…”
Section: Limites Na Formação Profissional Para Atendimento àS Mulhereunclassified